The foundations of the societal Peace in the Light of Surat Al-Hujurat (Islamic Sciences Journal, 2023)
Thank God, Lord of the worlds, and peace and prayers to our lord, the messengers, and to God and his companions.The Islamic society does not deviate from its human nature to some positions that deviate its members from the seriousness, expecting grudges and shipments with the resulting antagonism and quarrel and maybe a fight in some cases, Sura AL-Hujurat, which does not exceed eighteen verses is agreat Sura that contains a great list of the facts of religion or right This Sura has set the full contours of this life with a high, clean and sound world, including the rules, principles and essentials on which this world is based, If the whole world today seeks social stability, this blessed Sura has set the parameters of this social stability with the finest and most prestigious The phrase of this blessed surah laid out an integrated idea of the unity of humanity, the different races of the multi-fold, and then defined its unique features, which everyone does, the balance of God, which is exonered from the impurities of fancy and disorder.